Biological rehabilitation in the degraded land, a case study of Shariingol Soum of Selenge Aimag in Mongolia (Mongolian Journal of Agricultural Sciences, 2015)
Land is degraded and abandoned by intensive usages from mining and agriculture activities in the northern part of Mongolia. Especially agriculture land usage without rotation is one of the reasons of soil fertility loss. Land degradation is not only becoming an ecological degradation, but also decrease of economic benefits.We have conducted a survey on the planting perennial in the abandoned and degraded land. Planting perennials in the degraded lands is considering a one of the important technologies for plant regeneration (Institute of Geoecology, MAS. 2002). Lands are traditionally used for pasture and animal husbandry, but in recent decades multiple land use has increased rapidly in Mongolia. Especially, the mining activities have been implemented rapidly.From the result, we can see that, the wintering of Medicago falcata L is 70-76 percent and yield is 12-16.4 centner/ha in the abandoned land, and 80-85 percent for wintering and yield is 2-3.5 centner/ha in the degraded land from mining activities. Due to planting perennial, xerophyte plants increased by 12 percent and mesophyte plants increased by 45 percent in the abandoned land. In contrast, mesophyte plants decreased by 2 percent, and xerophyte plants decreased by 8 percent in the degraded land from mining activities.Journal of agricultural sciences №15 (02): 106-112, 2015